PENGARUH DANA PIHAK KETIGA TERHADAP PENYALURAN KREDIT PADA PD. BPR NTB SUMBAWA TAHUN 2010-2019 - U Usman; Nining Sudiyarti; Nydia Pratiwi Puji Lestari (Pusat Riset dan Publikasi, 2021)
This study aims to know the effect of third party funds toward credit distribution at PD. BPR NTB Sumbawa 2010-2019. The type of this study was associative study. The data used in this study were secondary data in the form of savings, deposit and credit at PD. BPR NTB Sumbawa in 2010-2019 which was collected through the documents that were already available. The data were analyzed using statistical analysis techniques, including multiple linear regression analysis, t and F tests and the coefficient of determination (R2) test. The results of study showed that partially savings had significant effect toward credit distribution at PD. BPR NTB Sumbawa 2010-2019. It was based on the result of t-test where t-value>t-table (2.657 2.364) with significant value of 0.033 which was lower than 0.05 (0.033?0.05), then deposits did not have significant effect toward credit distribution at PD. BPR NTB Sumbawa 2010-2019, it was based on the value of t-value < t-table (1.087<2.364) with significant value of 0.313 which was higher than 0.05 (0.313>0.05). Furthermore, simultaneously that savings and deposits had effect toward credit distribution at PD. BPR NTB Sumbawa, it was based on the value of the f-value>f-table (146.436>4.46) and significant value was 0.000 which was lower than 0.05 (0.000?0.05). Then the value of the coefficient of determination (R2) was 0.977 or 97.7%. It means that the percentage effect of savings and deposits toward credit distribution at PD. BPR NTB Sumbawa in 2010-2019 was 97.7%, while the remaining of 2.3% was affected by other variables out of this study.